Landslide Stability Analysis and Comprehensive Treatment Research - Ren, Suya (International Journal of Natural Resources and Environmental Studies, 2025)
Landslide disaster is a serious threat to human survival and reproduction, and will also cause adverse effects on the natural environment. In this paper, the influence factors of landslide are analyzed from rock and soil, rock mass structure, man-made and natural aspects. The methods of landslide stability analysis are introduced from qualitative, quantitative and semi-quantitative aspects. The principle of prevention and control of slippery slope is introduced. Prevention should be the main and treatment should be the auxiliary. The landslide control measures are introduced from the slope top surface water cut-off, anti-slide pile, anti-slide retaining wall, clamp rod (cable) reinforcement and so on. The landslide disaster occupies the first place in the natural disaster, so the in-depth study on the relevant problems of landslide control is of great significance to the guarantee of people’s life and property safety.